Effectiveness of Cardiopulmonary Resuscitation at the Workplace - Bellini, Lorenzo; Fagoni, Nazzareno; Andreassi, Aida; Sechi, Giuseppe Maria; Bonora, Rodolfo; Stirparo, Giuseppe (La Medicina del Lavoro, 2023)
Background: Out-of-Hospital Cardiac Arrest (OHCA) is a medical emergency whose chances of survival can be increased by rapid Cardiopulmonary Resuscitation (CPR) and early use of Public Access Defibrillators (PAD). Basic Life Support (BLS) training became mandatory in Italy to spread knowledge of resuscitation maneuvers in the workplace. Basic Life Support (BLS) training became mandatory according to the DL 81/2008 law. To improve the level of cardioprotection in the workplace, the national law DL 116/2021 increased the number of places required to be provided with PADs. The study highlights the possibility of a Return to spontaneous circulation in OHCA in the workplace. Methods: A multivariate logistic regression model was fitted to the data to extrapolate associations between ROSC and the dependent variables. The associations’ robustness was evaluated through sensitivity analysis. Results: The chance to receive CPR (OR 2.3; 95% CI:1.8-2.9), PAD (OR 7.2; 95% CI:4.9 - 10.7), and achieve Return to spontaneous circulation (ROSC) (crude OR 2.2; 95% CI:1.7-3.0, adjusted OR 1.6; 95% CI:1.2-2.2) is higher in the workplace compared to all other places. Conclusion: The workplace could be considered cardioprotective, although further research is necessary to understand the causes of missed CPRs and identify the best places to increase BLS and defibrillation training to help policymakers implement correct programming on the activation of PAD projects.